Analysis of Dispute Settlement Dynamics Analysis of behaviors in the import tariffdispute between the United States and China - Amelya, Cyndy; Ragika Diva Ayuningtyas; Muhammad Farid Rizky; Agatha, M. Aldy (JLAST : Journal of Law and Social Transformation, 2024)
The ongoing dispute over import tariffs between the United States and China has emergedas a significant concern within the global economy since 2018. Chinese retaliation, triggeredby the United States’ imposition of import taxes on Chinese imports as a response to unfairtrade practices including intellectual property theft and detrimental subsidies, furtherintensified global trade tensions. Both nations ultimately sought resolution of the importtariff dispute by appealing to the World Trade Organisation (W.T.O.). This study employs adescriptive qualitative approach, combining International Relations theory and caseanalysis to interpret the diplomatic strategy and conduct in settling this trade conflict.Analysis was conducted on data obtained from papers, official websites, and books toinvestigate the resolution of disputes through the World Trade Organisation (WTO) and theeconomic consequences of trade retaliation. The findings underscore the intricacy ofinternational economic relations, and the conduct exhibited by participants in managingconflicts. This study highlights the crucial significance of international organizations inpreserving trade stability and offers valuable understanding of the mechanisms involved inresolving disputes related to intricate import tariff conflicts.